Genetics and Social Determinants of Health as Drivers of Epidemiologic Variation in Sarcoidosis - Odackal, John; Crouser, Elliott D.; Sharp, Michelle; Cozier, Yvette C. (Seminars in Respiratory and Critical Care Medicine, 2025)
Sarcoidosis is a disease with high morbidity that has variable epidemiology based on genetics and sociodemographic factors. The etiology of this variability remains incompletely understood. This narrative review describes how genetics, social determinants of health, and the interactions between them may contribute to the differences in epidemiology and health outcomes observed in different patient groups with sarcoidosis.
Keywords: sarcoidosis; epidemiology; social determinants of health; genetics; pulmonary medicine; health disparities